Endoscopic enucleation of the prostate with Thulium Fiber Laser (ThuFLEP). A retrospective single-center study - Angelis Peteinaris; Vasileios Tatanis; Paraskevi Katsakiori; Theodoros Spinos; Solon Faitatziadis; Kristiana Gkeka; Anastasios Natsos; Theofanis Vrettos; Evangelos Liatsikos; Panagiotis Kallidonis (Archivio Italiano di Urologia e Andrologia, 2024)
Purpose: The aim of the present, retrospective study was to describe our initial experience and early outcomes of Thulium Fiber Laser enucleation of the prostate (ThuFLEP) with the use of the FiberDust™ (Quanta System, Samarate, Italy) in patients with benign prostate hyperplasia. Methods: From June 2022 to April 2023, all patients who underwent endoscopic enucleation of the prostate at Urology Department of the University Hospital of Patras were included. A single surgeon utilizing the same standardized operative technique performed all the surgeries. The primary endpoints included the uneventful completion of the operation, the surgical time and any minor or major complication observed intra- or post-operatively. Results: Twenty patients with benign prostate hyperplasia were treated with ThuFLEP. All the surgeries were completed successfully and uneventfully. The enucleation phase of the operation was completed in a mean time of 45 ± 9.1 min, while the average time needed for the morcellation was 17.65 ± 3.42 min. No significant complications were observed intra- or post-operatively. The average hemoglobin drop was calculated to be 0.94 ± 0.71 g/dL. Conclusions: All the operations were successfully and efficiently completed with the use of the FiberDust™ (Quanta System, Samarate, Italy) in ThuFLEP. Significant blood loss or major complications were not observed.